Pengaruh Promosi, Persepsi Harga, Keamanan dan Kemudahan terhadap Keputusan menggunakan Aplikasi Gojek di Jabodetabek - Sulastri Sulastri; Retno Suwiyanti; S. Tiwi Anggraeni (JUDICIOUS, 2022)
The development of technology and digitalization in various fields is progressing rapidly, one of the technological advances is the emergence of e-commerce applications that focus on the transportation, food delivery, and online payment sectors. GOJEK is one of the well-known and widely used apps in this category. The purpose of this study is to analyze the effect of promotion, price perception, safety, and comfort on the decision to use the GOJEK app in Jabodetabek. The analytical method used in this research is the quantitative data analysis method. The test stages carried out are: validity test, reliability test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, t test, f test, and determination coefficient. The data used in the research is in the form of a questionnaire, and 100 valid responses have been obtained. The sampling method used is non-probability sampling with a purposive sampling technique. The research results showed that Promotions did not affect the decision to use the GOJEK application. The price, safety, and convenience of GOJEK have an impact on people's decisions to use the app. The promotion, price perception, safety and convenience all affect the decision to use GOJEK simultaneously.